Weathers effect on the free space optics communication system - Fadhela Thaeer Mahmood; Alaa H. Ali; Alaa H. Ali Haeder (Institute of Advanced Engineering and Science, 2023)
Unlicensed spectrum is used in free space optics (FSO) communication, significantly increasing available bandwidth. Regardless of the weather, the most immediate concern is the link's performance and availability. Changes in the weather might impact the reliability of the link substantially. As a result, iterative optimization is being used to reduce the impact of weather and geography on FSO communication. In addition to enhancing visibility, this enhancement also reduces the bit error rate (BER). The system's wireless optical communication technology supports a data rate of up to 10 Gbps. The proposed wireless optical communication performance is compared to existing technologies regarding the visible distance, quality factor, BER, and eye diagram in various meteorological circumstances. Simulations show that the proposed work is more efficient.